(untitled) (Laisvalaikio tyrimai, 2022)
Relevance of the research topic. The relevance of this study lies in the fact that the impact of digitalization on the formation of value orientations in the conditions of the Fourth Industrial Revolution is becoming increasingly important, because we live in a digital era, which is determined by algorithms, bits, big data, reformatting the physical world. The purpose of the study is to conceptualize the formation of value orientations in the conditions of the Fourth Industrial Revolution, associated with the formation of the concept of a digital society, a digital person, digital culture and their influence on a person, his consciousness, worldview, culture, identity. The digital society is changing not only what we do, but also who we are and should become. The new technological revolution affects what values ​​a person has, how hierarchical structures are built, how human capabilities expand. Research objectives: 1) to reveal the model of thinking for the formation of the Fourth Industrial Revolution; 2) identify the conditions for the formation of the concept of a digital society, digital person, digital culture in the context of theoretical and methodological foundations; 3) justify the application of the methodology - a set of axiological, synergistic, cultural-creative methods necessary for deep penetration into the essence of digital values; 4) identify revolutionary innovations (from biotechnology to artificial intelligence) that redefine what it means to “be human” in the digital era and what are its value orientations. Digital technologies are pushing the modern boundaries of lifespan, health, cognition and potentiality in ways that were previously considered fantastic. Today we have to think about how to respond to new phenomena like the extension of life, "engineered children", the removal of information from human memory, and much more. Research result. A model of thinking is revealed, which is based on certain digital orientations for the formation of the Fourth Industrial Revolution. The conditions for the formation of a digital society, a digital person, a digital culture that affect the change in the values ​​of a digital society are identified. The application of the methodology is substantiated - a set of methods of axiological, synergistic, cultural-creative analysis necessary for deep penetration into the essence of the values ​​of the digital society. Revolutionary innovations (from biotechnology to artificial intelligence) have been identified that redefine what it means to “be human” in the digital age. Key words: digital society, digital society values, Fourth Industrial Revolution